The dark prophecy - Riordan, Rick (Riordan, Rick. Trials of Apollo, 2017)
Leaving the safety of the demigod training ground, a disgraced Apollo embarks on a quest across North America to find a dangerous ancient-world Oracle while navigating the challenges of the evil Triumvirate.